The impact of preoperative choroidal detachment on short-term surgical outcomes in highly myopic macular hole retinal detachment - Cai, Yi; Liu, Jia; Li, Xiaoxin; Zhao, Mingwei; Liang, Jianhong; Yin, Hong; Yu, Wenzhen; Qi, Huijun; Qian, Tong; Shi, Xuan; Qu, Jinfeng; Cheng, Yong; et al. (Frontiers in Medicine, 2025)
PurposeTo evaluate the impact of choroidal detachment on short-term surgical outcomes in highly myopic macular hole retinal detachment (MHRD) and to discern the risk factors associated with macular hole (MH) closure.MethodsA retrospective analysis was carried out on 104 highly myopic MHRD eyes that underwent vitrectomy and intraocular tamponade. Patients were stratified according to the presence or absence of preoperative choroidal detachment. Demographic data, preoperative ocular parameters, and postoperative outcomes were compared. Logistic regression analysis was employed to identify risk factors for MH closure.ResultsNo significant differences were observed in age or disease duration between groups. Preoperative visual acuity was inferior in the choroidal detachment group (2.19 ± 0.70 LogMAR vs. 1.78 ± 0.60 LogMAR, p = 0.013), and preoperative intraocular pressure (IOP) was significantly lower (9.05 ± 3.73 mmHg vs. 13.18 ± 4.15 mmHg, p < 0.001). Postoperatively, the choroidal detachment group demonstrated worse vision outcome (1.52 ± 0.49 LogMAR vs. 1.22 ± 0.38 LogMAR, p = 0.004) and a substantially higher rate of rescue therapy (28.6% vs. 3.6%, p = 0.002). The rate of MH closure was comparable between groups (41.0% vs. 42.9%, p = 1.000). Logistic regression identified advanced age (β = 0.099, p = 0.001) and lower preoperative IOP (β = −0.132, p = 0.031) as favorable factors for MH closure.ConclusionChoroidal detachment exerts an adverse impact on postoperative visual acuity and is associated with a significantly higher rate of rescue surgical intervention. Younger age and higher preoperative intraocular pressure (IOP) may impede MH closure.